Numerical study of the dynamic expansion behaviour of 9 mm expansion bullets in gelatine. (December 2021) - Jiang, Mingfei; Li, Zhongxin; Liu, Kun; Zhang, Ruijie; Wu, Zhilin
Highlights: The penetration process of expansion bullets in gelatine can be divided into four stages. Twenty bullet configurations with different parameters were considered. Expansion bullets cannot completely expand when they travel at speeds lower than the critical velocity, but they over-expand when they travel at speeds higher than the threshold velocity. Abstract: Due to their limited penetration power, expansion bullets are known for their good effectiveness and less endangerment to bystanders, thereby playing an important role in the fight against terrorism and violence. This study considered 20 bullet configurations with different shape parameters influencing the motion and deformation of 9 mm expansion bullets in gelatine. Owing to the constraints of high-speed photography, experimental observations have limitations. However, through numerical simulation, this study found that the penetration process of the 9 mm expansion bullets through biological tissues, as represented by the gelatine block in this study, can be subdivided into four stages. Further, the expansion bullet is highly sensitive to the impact velocity, and did not completely expand when travelling at speeds below the critical velocity and over-expanded when travelling at speeds above the threshold velocity. The results of this study revealed the interaction mechanism between expansion bullets and gelatine, which are significant to ballistic wounding assessment and treatment of expansion bullets.